Social Sciences, Arts And Humanities Research Collaboration: The Malaysian Coverage - Hussain, Husriati (2014)
As a developing country, Malaysia emphasizes the need for university researchers to be more socially oriented and highly encourages them to seek collaboration with other organizations. Collaboration is used as the main requirement and indicator in almost Malaysian grant scheme and Malaysian research assessment, such as Higher Institutions Centre of Excellence (HICoE) Grant, Long Term Research Grant Scheme (LRGS), Malaysian Research Assessment (MyRA), National Higher Education Strategic Plan, etc. The main reasons behind this are because collaboration may contribute to creative, wealth and innovative ideas, unique experiences, and great exposures, which consequently will give a high impact on the nation's research productivity and development. In this regard, this study employed bibliometric methods of co-authorship analysis to measure the patterns of collaboration in Social Sciences, Arts and Humanities in Malaysia from 2007 to 2011. Based on the 2,280 publications, patterns of collaboration were analyzed with respect to 7 relevant areas: co-authorship patterns, national and international collaboration, country collaboration, institutional collaboration, sectoral collaboration, intra-disciplinary and interdisciplinary collaboration, and extent of collaboration. The results may help the government and universities to plan an appropriate Malaysia Research Policy and manage the R&D funding and resources effectively and efficiently. The